Analisis Social Comparison dan Life Satisfaction pada Mahasiswa Tingkat Akhir dari Perspektif Sosiologi Komunikasi - Ramadhani, Nabyla Octa; Purnamasari, Devi (Jurnal Komunikasi Nusantara, 2025)
Final-year students are in a complex transition phase marked by academic pressure, career uncertainty, and high social expectations. In this situation, social comparison often functions as part of symbolic and intrapersonal communication processes through which students evaluate their position in society. This study aims to analyze the reasons why students engage in social comparison and its impact on life satisfaction, positioning their subjective experiences within the context of sociology of communication. The research employed a descriptive qualitative approach with a phenomenological method. Data were collected through in-depth interviews, observations, and documentation involving six final-year students in Semarang City from various universities and work backgrounds. The findings indicate that social comparison arises both consciously and unconsciously in students’ communication processes, either as self-reflection or as a response to external social pressures, including those from social media. Upward comparison tends to trigger feelings of lagging behind, anxiety, and dissatisfaction, while downward comparison can foster gratitude. Life satisfaction is influenced by how individuals interpret these comparisons and the extent of social support they receive. This study emphasizes the importance of awareness of symbolic and intrapersonal communication processes in managing social comparison, so that students can maintain their emotional and social well-being during the final stage of their studies. Abstrak Mahasiswa tingkat akhir berada dalam fase transisi yang kompleks, ditandai oleh tekanan akademik, ketidakpastian karier, dan ekspektasi sosial yang tinggi. Dalam situasi ini, perbandingan sosial (social comparison) sering kali menjadi bagian dari proses komunikasi simbolik dan intrapersonal untuk mengevaluasi posisi diri dalam masyarakat. Studi ini bertujuan untuk menganalisis alasan mahasiswa melakukan perbandingan sosial dan dampaknya terhadap kepuasan hidup (life satisfaction), dengan menempatkan pengalaman subjektif mereka dalam konteks sosiologi komunikasi. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode fenomenologi. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi terhadap enam mahasiswa tingkat akhir di Kota Semarang dari berbagai perguruan tinggi dan latar belakang pekerjaan. Temuan menunjukkan bahwa social comparison muncul secara sadar maupun tidak sadar dalam proses komunikasi mahasiswa, baik sebagai refleksi diri maupun akibat tekanan sosial eksternal, termasuk media sosial. Upward comparison cenderung memicu rasa tertinggal, kecemasan, dan ketidakpuasan, sedangkan downward comparison dapat menumbuhkan rasa syukur. Tingkat kepuasan hidup dipengaruhi oleh bagaimana individu memaknai perbandingan tersebut serta sejauh mana mereka memperoleh dukungan sosial. Studi ini menegaskan pentingnya kesadaran akan proses komunikasi simbolik dan intrapersonal dalam mengelola perbandingan sosial agar mahasiswa mampu menjaga kesejahteraan emosional dan sosial mereka di masa akhir studi.